2022
DOI: 10.3389/fnut.2022.1071515
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of cinnamon, ginger, and metformin consumption on metabolic health, anthropometric indices, and sexual hormone levels in women with poly cystic ovary syndrome: A randomized double-blinded placebo-controlled clinical trial

Abstract: Background/objectivesPolycystic ovary syndrome (PCOS) is a prevalent endocrine disorder in women that can alter blood glucose, lipid profile and sexual hormonal level. Therefore, the evaluation of potential therapeutic agents in this population is important. The aim of the study was to determine the effects of cinnamon, ginger, and metformin intake on improvement of sex hormones level, metabolic health (lipid profiles, insulin level and fasting blood glucose) and anthropometric indices (weight, body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Levels of progesterone, estradiol, LH, and FSH were increased significantly compared to the control [22]. Ginger supplementation (500 mg of ginger, 3 × day) in a study with 100 women with PCOS showed significant decreases in FSH (follicle-stimulating hormone) and LH (Luteinizing hormone) levels compared to the placebo, while a cinnamon supplementation of 500 mg 3 × day lowered testosterone levels [31].…”
Section: The Effects Of Ginger and Cinnamon On Sex Hormonesmentioning
confidence: 91%
“…Levels of progesterone, estradiol, LH, and FSH were increased significantly compared to the control [22]. Ginger supplementation (500 mg of ginger, 3 × day) in a study with 100 women with PCOS showed significant decreases in FSH (follicle-stimulating hormone) and LH (Luteinizing hormone) levels compared to the placebo, while a cinnamon supplementation of 500 mg 3 × day lowered testosterone levels [31].…”
Section: The Effects Of Ginger and Cinnamon On Sex Hormonesmentioning
confidence: 91%
“…There were 41 studies looking at the benefits of culinary doses of cinnamon. Ten in healthy individuals [46,[48][49][50][54][55][56][57]81,82], nineteen in those with diabetes [47,53,[59][60][61]63,64,[66][67][68][69][70][71][74][75][76]78,79,84], six in women with PCOS [58,65,72,73,80,83], one in Asian Indians with MetS [77], one in patients with NAFLD [62], one in individuals with impaired glucose tolerance [51], one in sedentary women with obesity [52], one in women with dyslipidaemia [86] and one in prediabetic individuals [166]. Doses ranged from 1 to 6 g, either as a single dose or daily for between 2 weeks and 6 months.…”
Section: Cinnamonmentioning
confidence: 99%
“…Beneficial effects on insulin were found in 4 randomized cross-over studies, 10 doubleblind RCTs and 1 single-blind RCT from doses of 1-3 g/day or single doses of 3-6 g of cinnamon [46,48,49,57,59,62,68,70,73,75,[77][78][79][80]83], while 6 double-blind RCTs, 1 singleblind RCT and 1 randomized cross-over study found no effect from doses of 1-1.5 g/day or a single dose of 6 g [47,49,51,53,60,67,71,166].…”
Section: Cinnamonmentioning
confidence: 99%
See 1 more Smart Citation